Understanding sedimentation trends to enhance sustainable reservoir management in the Angereb reservoir, Upper Blue Nile Basin, Ethiopia - Tessema, Yoseph M.; Zimale, Fasikaw A.; Kebedew, Mebrahtom G. (Frontiers in Water, 2024)
Reservoir sedimentation is a significant issue that shortens reservoir life and impacts operations such as irrigation, hydropower, and drinking water supply because it significantly reduces the reservoir's initial capacity. Information on changes in the storage capacity is required to reduce the risk of reservoir sustainability. This study was conducted on the Angereb reservoir in the sub-humid region of Ethiopia, in the Upper Blue Nile Basin. Bathymetric surveys and ArcGIS 10.8 were used to estimate the sedimentation and service life of the Angereb reservoir. A Triangulated Irregular Network (TIN) surface was developed from the survey data to estimate the volume of the reservoir. Based on the findings of this bathymetry a total of 2.18 Mm 3 of sediment was deposited on the reservoir bed between 2007 to 2022. Storage capacity was decreased by 62.28% in 15 16 years of operation and caused an average annual volume reduction of 3.94.15%. The sediment yield (SY) and specific sediment yield (SSY) of the Angereb watershed revealed 192715.5 and 170312.5 159,112.5 m 3 year -1 and 3043.2 and 2689.4 2512.54-ton km -2 year -1 for trap efficiencies of 70.1% and 80% calculated with two methods, respectively. The SSY has increased by about 50.3% to the minimum and 70.1% 60.5% to the maximum indicating more degradation of the watershed in fifteen sixteen years. The gross storage capacity loss of the reservoir was about 75% which was (5.3 Mm 3 in 1997 and reduced to 1.32 Mm 3 in 2022) with an annual reduction of 32.9% in storage capacity. The reservoir will be filled up by sediment in 7 years if the incoming sediment remains the same in the future. These findings will serve as a call for action in the watershed and a foundation for managing the accumulated sedimentation in the Angereb reservoir and for developing sediment control and management strategies for similar reservoirs.